How do female entrepreneurs perform? Evidence from three developing regions - Bardasi, Elena; Sabarwal, Shwetlena; Terrell, Katherine (Small Business Economics, 2011)
Using the World Bank Enterprise Survey data, we analyze performance gaps between male- and female-owned companies in three regions—Eastern Europe and Central Asia (ECA), Latin America (LA), and Sub-Saharan Africa (SSA). Among our findings are significant gender gaps between male- and female-owned companies in terms of firm size, but much smaller gaps in terms of firm efficiency and growth (except in LA). Part of the reason women run smaller firms is that they tend to concentrate in sectors in which firms are smaller and less efficient (in ECA and SSA). By contrast, we find no evidence of gender discrimination in access to formal finance in any of the three regions, although in ECA women are less likely than men to seek formal finance. Finally, while female entrepreneurs receive smaller loans than their male counterparts, the returns from each dollar they receive is no lower in terms of overall sales revenue.
Number: 4
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Gender and the Business Environment for New Firm Creation - Klapper, Leora F.; Parker, Simon C. (The World Bank Research Observer, 2011)
Abstract. The authors summarize the extant literature on the relationship between gender and entrepreneurship. They note significant quantitative gender differ
Number: 2 Publisher: Oxford Academic
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

The Preparatory Survey on Nacala Port Development Project in the Republic of Mozambique Final Report - JICA (Japan International Cooperation Agency (JICA), 2011)
Japan International Cooperation Agency (JICA) decided to conduct the preparatory survey on Nacala Port Development Project in the Republic of Mozambique, and organized a survey team headed by Dr. Kobune of Ides and consists of OCDI, Oriental Consultants, ECOH CORPORATION, and Ides between June, 2010 and April, 2011. The survey team held a series of discussions with the officials concerned of the Government of the Republic of Mozambique, and conducted field investigations. As a result of further studies in Japan, the present report was finalized. I hope that this report will contribute to the promotion of the project and to the enhancement of friendly relations between our two countries. The Study Team compiled this report, which proposed the Medium and Long-term Development Plan of Nacala Port with the target year of 2030 and the Short-term Development Plan, and selected the Urgent Rehabilitation Project through close consultations with officials of the Mozambique Government, in particular, Ministry of Transport and Communications (MTC), Portos e Caminhos de Ferro de Mocambique E.P. (CFM), as well as the Management of Corredor de Desenvolvimento do Norte (CDN), and authorities concerned.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

Prioritising PPCR Investments in Mozambique: The Politics of ‘Country Ownership’ and ‘Stakeholder Participation’ - Shankland, Alex; Chambote, Raul (2011)
Mozambique is both one of the poorest countries and one with the highest level of vulnerability to multiple potential consequences of climate change, including drought, flood, sea level rise and increased frequency and severity of tropical cyclones – making it a natural candidate for inclusion in the Pilot Program for Climate Resilience (PPCR), which aims to help poorer countries to integrate climate change response into their national development processes. This article examines the process of prioritising investments under the PPCR in Mozambique, and asks to what extent this process has demonstrated the ‘country ownership’ and ‘broad participation’ which the PPCR claims to promote. It particularly focuses on the coastal cities component of the programme, and the question of whether the opposition-controlled port city of Beira should receive priority in PPCR investments.
Accepted: 2016-01-08T12:21:16Z Publisher: Blackwell Publishing Ltd
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP)

Desafios para Moçambique - 2011 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Francisco, António (Instituto de Estudos Sociais e Económicos, 2011)
PARTE I – POLÍTICA ESTADO, DESCENTRALIZAÇÃO E CIDADANIA – EQUAÇÃO POSSÍVEL OU IMPERATIVA? / José Óscar Monteiro “TRANSFORMAÇÕES SEM MUDANÇAS?” OS CONSELHOS LOCAIS E O DESAFIO DA INSTITUCIONALIZAÇÃO DEMOCRÁTICA EM MOÇAMBIQUE / Salvador Cadete Forquilha | Aslak Orre DESCENTRALIZAÇÃO EM CONTEXTO DE PARTIDO “DOMINANTE” – O CASO DO MUNICÍPIO DE NACALA PORTO / Domingos do Rosário REVISÃO DA LEGISLAÇÃO ELEITORAL – ALGUMAS PROPOSTAS PARA O DEBATE / Luís de Brito PARTE II – ECONOMIA DESAFIOS DA MOBILIZAÇÃO DE RECURSOS DOMÉSTICOS – REVISÃO CRÍTICA DO DEBATE / Carlos Nuno Castel-Branco DESAFIOS DE EXPANSÃO DAS RECEITAS FISCAIS EM MOÇAMBIQUE / Rogério Ossemane FINANCIAMENTO DO ESTADO COM RECURSO À DÍVIDA – PROBLEMAS E DESAFIOS / Fernanda Massarongo | Carlos Muianga DESAFIOS DA EXPANSÃO DE SERVIÇOS FINANCEIROS EM MOÇAMBIQUE / Sofia Amarcy | Nelsa Massingue “7 MILHÕES” – REVISÃO DO DEBATE E DESAFIOS PARA DIVERSIFICAÇÃO DA BASE PRODUTIVA / Zaqueo Sande PARTE III – SOCIEDADE TER MUITOS FILHOS, PRINCIPAL FORMA DE PROTECÇÃO SOCIAL NUMA TRANSIÇÃO DEMOGRÁFICA INCIPIENTE – O CASO DE MOÇAMBIQUE / António Francisco PROTECÇÃO SOCIAL FINANCEIRA E DEMOGRÁFICA – DESAFIOS PARA UMA SEGURANÇA HUMANA DIGNA EM MOÇAMBIQUE / António Francisco | Rosimina Ali | Yasfir Ibraimo POLÍTICAS DE HIV E SIDA E DINÂMICAS SOCIOCULTURAIS EM MOÇAMBIQUE – NOTAS PARA REFLEXÃO /Sandra Manuel PARTE IV – MOÇAMBIQUE NO MUNDO SADC – COOPERAÇÃO E SEGURANÇA PÚBLICA / João Paulo Borges Coelho AS ECONOMIAS “EMERGENTES” NO SECTOR AGRÍCOLA MOÇAMBICANO – LEITURAS, IMPLICAÇÕES E DESAFIOS / Sérgio Chichava DEPENDÊNCIA DE AJUDA EXTERNA, ACUMULAÇÃO E OWNERSHIP – CONTRIBUIÇÃO PARA UM DEBATE DE ECONOMIA POLÍTICA / Carlos Nuno Castel-Branco
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Ten years of single window implementation: lessons learned for the future - Koh, Jonathan (Global Trade Facilitation Conference 2011, 2011)
This paper examines the Single Window concept and its developments in practice over the last 10 years and provides an analysis of its development over time. An overview of the emerging information technology that would impact its future development is also presented. The paper also examines regional trends in Single Window implementation, based on a survey of tenders documents issued by various countries in the recent years. Finally, it offers an outlook on its future development and provides a number of recommendations.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Accountability Through Dialogue: The Presidencîa Aberta E Inclusiva In Mozambique - Leininger, Julia (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Accountability is a central feature of democracy. Governments must explain what they are doing, justify why they are doing certain things and not others. Moreover, accountability increases the likelihood of the improvement of public services if citizens have the political scope to hold politicians and administrators accountable, and potentially sanction them. Consequently, developing countries as well as the OECD-donor community have committed themselves to working towards the improvement of domestic accountability in developing countries. In many developing countries, accountability is exercised through both formal and informal institutions. This paper summarises the results of an empirical study on accountability in Mozambique. It focuses on the Presidência Aberta e Inclusiva (PAI, Open and Inclusive Presidency), a legally not codified institution for accountability introduced by President Armando E. Guebuza. It provides a public forum for the president to engage in a dialogue with the population and the local administrations, in combination with an ongoing process of decentralisation. This study shows that the interaction between formal and more informal institutions has a mixed influence on policymaking and democracy. Overall, there is an untapped potential to improve the PAI as an institution for accountability that strengthens formal institutions.
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação

Abastecimento De Água Nas Zonas Rurais: Avaliação Dos Progressos Para a Prestação De Serviços Sustentáveis - Munguambe, Carlos Gideon José; Jesus, Vitória Afonso Langa de (IRC International Water and Sanitation Centre, 2011)
This study presents an analytical ‘picture’ of the rural water sub-sector in Mozambique, describing the legal framework, mechanisms for coordination, harmonisation, funding, accountability, participation and supervision. The study was commissioned for the Sustainable Services at Scale, or Triple-S, initiative, which aims to contribute to improving the sustainability of global rural water supply. According to the general population census carried out in 2007, Mozambique had a total population of 20,226,296, 70.2% of whom live in rural areas, with a water coverage rate of only 54%.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; health - WASH / saúde - água; higiene e saneamento; health / saúde

Decentralization and Economic Performance in Indonesia - Pepinsky, Thomas B.; Wihardja, Maria M. (Journal of East Asian Studies, 2011)
Indonesia's 1999 decentralization law gave local governments in Indonesia an unprecedented opportunity to adopt prodevelopment policies. In this article, we study whether decentralization has in fact generated improved economic performance in Indonesia. Using a synthetic case control methodology, we argue that Indonesian decentralization has had no discernable effect on the country's national-level economic performance. To explain why not, we use subnational data to probe two political economy mechanisms-interjurisdictional competition and democratic accountability-that underlie all theories linking decentralization to better economic outcomes. Our findings suggest that extreme heterogeneity in endowments, factor immobility, and the endogenous deterioration of local governance institutions can each undermine the supposed development-enhancing promises of decentralized government in emerging economies such as Indonesia.
Number: 3
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Local economic governance: a survey of business operators in 245 districts/municipalities in Indonesia, 2011 - The Asia Foundation; Regional Autonomy Watch (The Asia Foundation, 2011)
Decentralization has been underway in Indonesia for more than ten years, but recently many have challenged the how effectively decentralization – and even democratization – is being implemented. Deterioration in the quality of public services, the many corruption cases involving local governments, and low economic growth rates in some regions have prompted discourse about whether the country is making a reversal away from decentralization and democratization. We recognize that the move toward regional autonomy has not been without its faults. Nevertheless, a choice was made to strengthen democracy and move towards local autonomy based on the problems created by the centralistic, authoritarian system of the previous regime. Yet it is unfair to judge regional autonomy a failure after it has been implemented for such a short time, and under a somewhat inconsistent policy framework. Since 2001, the Regional Autonomy Watch (KPPOD) and The Asia Foundation have aimed to present a clear picture of the quality of regional economic governance from the perspective of business owners. Our studies provide input to government at the central, provincial and regional/municipal levels, as well as information to other stakeholders regarding efforts that can be undertaken to promote improve economic growth under regional autonomy. This year’s study finds significant variation among regions in the quality of economic governance. This indicates that despite many limitations, some regions have used the opportunities provided by autonomy to foster good governance while others have not. It is hoped that this present study, and the awards presented to regencies and municipalities with the best performance, will promote a healthy competition among regional leaders. It is also envisioned that local governments whose performance is still low can learn from their neighbors who are doing better, and be inspired to improve. We recognize that improving economic governance requires a strong commitment and hard work, not only from the heads of regions but from all ranks of government officials, politicians, business owners and other stakeholders. This study can help set priorities for reform of local economic governance, identifying areas for immediate improvement that are relatively easy to achieve but have the potential of significant impact. Other aspects may need more time for improvement.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; M - survey / inquérito; Northern PEA; decentralization / descentralização